Diversity of Escherichia coli found in the Salish Sea - Grunwald, Jenny L.; Rabinowitz, Peter; Weissman, Scott J.; Roberts, Marilyn C. (Frontiers in Marine Science, 2022)
E. coli is a species of enteric bacteria found in the intestinal tract of humans and animals that can persist in the environment and contaminate food. Anthropogenic activity has led to pathogenic E. coli from humans and animals contaminating environments through the discharge of fecal wastes in sewage and agricultural runoff. While anthropogenic sources of E. coli have been described in terrestrial and freshwater environments, gaps remain in scientific knowledge about E. coli diversity in marine environments and the risk to human and animal health. This study aims to fill in some of the knowledge gaps on the diversity of E. coli in marine ecosystems, including: 1) describe the spatial variation of the E. coli sequence types (STs) found in the study region; 2) describe available information on E. coli STs from marine environments in terms of known relationships to determine if the isolates were related to human, animal, environment strains or novel. We analyzed a dataset of 332 E. coli isolates from the Salish Sea ecosystem, comprising 196 multi-locus sequence types. Sample sources included marine water near shellfish beds, marine wildlife, river otters, and a small number of marine water sites near beaches and freshwater samples from creeks into the Salish Sea. ST10 was the most frequent ST (n=12) and was found in multiple locations and sample types. For the identified STs, we searched metadata for E. coli STs in EnteroBase, an international E. coli database. Additional information on E. coli STs was derived from searches of published studies in PubMed. We found that diversity varied between different regions of the study area, with the greatest diversity found in an area which has partially treated wastewater outflows. A higher diversity of STs associated with animals was found in an area near were animals are raised. Many of the STs identified have been associated with virulence in humans. For a number of identified STs, no references could be found in either PubMed or EnteroBase. These findings support the importance of further studies to understand the relevance of marine E. coli to human and wildlife health.